Heat-insulating waterproof asphalt mixture and preparation method thereof
By mixing SBS modified asphalt with magnesium salt, basalt fibers, titanium boronide particles and foaming to form a composite silica aerogel and coating the sealant on the surface, the urban 'heat island effect' and asphalt materials are solved. The problem of insufficient waterproofing and heat insulation achieves efficient heat insulation and waterproofing effects.
Patent Information
- Application Number
- CN202411394703.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-02-14
AI Technical Summary
The existing technology is difficult to effectively solve the urban ‘heat island effect’ phenomenon, leading to energy waste and health problems, and asphalt materials have shortcomings in waterproofing and heat insulation.
By mixing SBS modified asphalt with magnesium salt, basalt fibers, titanium bored particles and foaming treatment, a composite silica aerogel is formed, and finally coated with sealant on the surface to prepare a heat-insulated and waterproof asphalt mixture. .
It achieves significant heat insulation and waterproofing effects. Through the well-developed bubble cells and mechanical support, the stability and waterproof performance of the material are enhanced, while reducing thermal conductivity and reducing energy waste.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, in particular to a heat-insulating and waterproof asphalt mixture and a preparation method thereof. Background Art
[0002] Since the beginning of the 21st century, the world economy has maintained rapid growth, in which construction and highway development have played a key role. Asphalt is the oldest and most widely used coating and pavement cementing material. Its demand has increased exponentially with the rapid development of the economy. Because of its good adhesion, insulation, heat insulation, moisture-proof, seepage-proof, waterproof, anti-corrosion, and rust-proof properties, it has a wide range of uses besides paving. When building a shelter, asphalt is often used as a waterproof layer. When building a cold storage, asphalt and wood chips are often mixed to make an insulation layer; applying asphalt on railway sleepers can prevent corrosion; applying asphalt on underground pipelines can prevent rust; laying a layer of asphalt on reservoirs and dams can prevent seepage and leakage; injecting asphalt into the joints of bridge decks can play a role in thermal expansion and contraction. Asphalt can also be mixed with other materials to make asphalt paint, asphalt felt, asphalt rubber, asphalt coating, asphalt insulation glue and other products. With the development of modern science and technology, the use of petroleum asphalt has become more extensive. In terms of building materials, mixing asphalt with soil can make asphalt bricks and asphalt boards with high strength, low water absorption, beautiful and durable, which is a new type of building material. In agriculture, spraying asphalt and fertilizer on the soil surface after mixing can keep warm, reduce water evaporation, and prevent fertilizer loss. In the electrical industry, asphalt can be used as an insulating material and cable protective layer, especially underground cables and underwater cables. In addition, if asphalt is further processed, it can be used to produce petroleum coke necessary for the steelmaking industry, and can also provide carbon fiber necessary for the manufacture of spacecraft. It can be seen that asphalt has a wide range of uses. It can also be regarded as an unknown hero in human beings' transformation and conquest of nature; and with the development of urbanization, the phenomenon of urban "heat island effect" has become increasingly prominent. This phenomenon has seriously affected people's production and life, not only affecting people's health and life, but also causing a lot of energy waste. The phenomenon of urban "heat island effect" is directly related to the city's pavement. A large number of artificial structures such as paved ground and various building walls have changed the thermal properties of the city's underlying surface, accumulated a large amount of solar heat energy and radiated outward, which is one of the main factors causing the urban "heat island effect". Summary of the invention
[0003] The object of the present invention is to provide a heat-insulating and waterproof asphalt mixture and a preparation method thereof, so as to solve the problems existing in the prior art.
[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a heat-insulating and waterproof asphalt mixture, which is prepared by mixing asphalt with magnesium salt, basalt fiber, and titanium boride particles and foaming them, and then compounding silica aerogel, and finally coating the surface with a sealing agent.
[0005] Furthermore, a method for preparing a heat-insulating and waterproof asphalt mixture comprises the following preparation steps:
[0006] (1) Grind the SBS modified asphalt until it passes through a 80-mesh sieve, heat it to 180-220°C in a nitrogen atmosphere, stir it at 150-240 rpm for 30-80 min, heat it to 300-380°C, continue stirring for 30 min, heat it to 400-450°C, and keep it warm for 2-6 h to obtain intermediate A;
[0007] (2) Grinding the intermediate A to pass through a 100-150 mesh sieve, adding basalt fiber, titanium boride particles, and magnesium acetate, heating to 280-300° C., stirring at 200 rpm for 3-6 hours, and then adding toluene for supercritical foaming treatment to obtain an asphalt foam material;
[0008] (3) Silica sol and asphalt foam material are mixed, the pH value of the solution is adjusted to 6-7 with ammonia water, and dried at 75-85° C. for 4-8 hours to obtain a composite material. Then, a sealing agent is applied to the surface of the composite material and cured at room temperature for 25-50 hours to obtain a heat-insulating and waterproof asphalt mixture.
[0009] Furthermore, the length of the basalt fiber in step (2) is 6 mm.
[0010] Furthermore, the particle size of the titanium boride particles in step (2) is 0.5 to 3 μm.
[0011] Furthermore, in step (2), the mass ratio of the intermediate A, basalt fiber, titanium boride particles, magnesium acetate and toluene is 60-100:5-10:5-10:0.1-0.5:0.2-0.4.
[0012] Furthermore, the process parameters of the supercritical foaming treatment in step (2) are: nitrogen gas, 300° C., and 3 MPa.
[0013] Furthermore, the preparation method of the silica sol in step (3) is as follows: ethyl orthosilicate, deionized water and ethanol are mixed in a molar ratio of 1:4.5:10, heated to 60° C., stirred at 100 rpm for 40 to 70 min, and the pH value of the solution is adjusted to 3 to 4 with hydrochloric acid to obtain the silica sol.
[0014] Furthermore, in step (3), the mass ratio of the silica sol to the asphalt foam material is 5 to 10:1.
[0015] Furthermore, the preparation method of the sealing agent in step (3) is as follows: propyltrimethoxysilane, ethanol, dibutyltin dilaurate and deionized water are mixed in a mass ratio of 20:20:0.3:4, heated to 70-90°C, reacted for 3-5 hours, the pH value of the solution is adjusted to 7 with aqueous ammonia, and then the ethanol and unreacted water are distilled off at 90°C, then the temperature is raised to 110°C, the reaction is continued for 1-2 hours, cooled to room temperature, 1.1-1.5 times the mass of propyltrimethoxysilane is added to dissolve in ethanol, filtered, and the liquid is obtained.
[0016] Furthermore, the amount of the sealing agent in step (3) is 10 to 20 mL / m 2 .
[0017] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0018] The asphalt mixture of the present invention is prepared by mixing mesophase asphalt with magnesium salt, basalt fiber and titanium boride particles and foaming them, then compounding silica aerogel, and finally coating the surface with a sealing agent to achieve heat insulation and waterproof effects.
[0019] Firstly, SBS modified asphalt is used as the matrix material. After heat treatment, the amorphous anisotropic components in the asphalt are reduced, and the isotropic intermediate phase asphalt is increased and dispersed in the raw asphalt to form a relatively regular polycyclic aromatic hydrocarbon group structure, which is beneficial for the matrix to form well-structured and evenly distributed bubbles in the supercritical foaming process, and achieve the effects of heat insulation and waterproofing. By adding magnesium elements, basalt short fibers, and titanium boride particles, mechanical support is formed at the interface, and the solid phase material will be adsorbed on the gas-liquid interface or mixed in the bubble wall liquid. The local bending stress generated on the bubble wall surface is used to balance the pressure difference of the internal liquid Plateau boundary and damp the fluctuation of the bubble wall thickness, thereby preventing the bubble wall from further rupture and increasing the foaming performance. Strong structural stability. The basalt fiber has a large aspect ratio and its endpoints are interconnected. Through mechanical contact, it forms a three-dimensional network structure, which acts as a support connection in the asphalt matrix. During the foaming process, it prevents the thinning and rupture of the bubble wall caused by thermal fluctuations or mechanical vibrations at the gas-liquid interface on both sides of the bubble wall, thereby strengthening the integrity and stability of the pore structure. Magnesium is highly active in the melt. By reducing the surface tension of the asphalt melt, it improves the wettability of the solid component and the matrix. Magnesium has a stabilizing effect on liquid foam, which allows the pores to nucleate and grow rapidly, and assists the titanium boride particles to be located in the bubble wall, accelerating the homogenization of the pore size, presenting a typical dry foam morphology, and ultimately further enhancing the waterproofness and thermal insulation of the matrix.
[0020] Secondly, the aerogel formed by silica sol is filled in the pore structure of the matrix, thereby reducing the porosity and enhancing the matrix's resistance to water damage. At the same time, a part of the phonons originally transmitted in the foam skeleton enters the amorphous aerogel nano-network structure. The transmission of these phonons has to go through a nearly infinitely long distance, and the transmission process is greatly hindered, thereby further enhancing the thermal insulation performance of the matrix by reducing the thermal conductivity. Next, the silicone material is used as a sealing agent, coated on the surface of the substrate, and cured into a film to form a good closed network, making it difficult for water molecules to wet and retain on the surface of the substrate, and then partially penetrate into the asphalt mixture, blocking the tiny gaps inside the asphalt mixture to form a complete waterproof network structure, thereby greatly reducing the possibility of water damage to the asphalt mixture. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0022] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the heat-insulating and waterproof asphalt mixture prepared in the following examples are as follows:
[0023] Waterproof: Take the embodiment and the comparative example of the same size and test their waterproof effects according to GB / T328.10.
[0024] Thermal insulation: The thermal conductivity of the embodiment and the comparative example of the same size was tested at different temperatures using a TPS2500s thermal conductivity meter.
[0025] Example 1
[0026] (1) Grind the SBS modified asphalt until it passes through a 80-mesh sieve, heat it to 180°C in a nitrogen atmosphere, stir it at 150 rpm for 30 min, heat it to 300°C, continue stirring for 30 min, heat it to 400°C, and keep it warm for 2 h to obtain intermediate A;
[0027] (2) Grind the intermediate A until it passes through a 100-mesh sieve, add basalt fiber with a length of 6 mm, titanium boride particles with a particle size of 0.5 μm, and magnesium acetate, heat to 280° C., stir at 200 rpm for 3 h, and then add toluene to perform supercritical foaming treatment. The process parameters are: nitrogen gas, temperature of 300° C., and air pressure of 3 MPa to obtain an asphalt foam material; the mass ratio of the intermediate A, basalt fiber with a length of 6 mm, titanium boride particles with a particle size of 0.5 μm, magnesium acetate, and toluene is 60:5:5:0.1:0.2;
[0028] (3) TEOS, deionized water, and ethanol were mixed in a molar ratio of 1:4.5:10, heated to 60°C, stirred at 100 rpm for 40 min, and the pH of the solution was adjusted to 3 with hydrochloric acid to obtain silica sol; propyltrimethoxysilane, ethanol, dibutyltin dilaurate, and deionized water were mixed in a mass ratio of 20:20:0.3:4, heated to 70°C, reacted for 3 h, and the pH of the solution was adjusted to 7 with ammonia water, and then the ethanol and unreacted water were distilled off at 90°C, then heated to 110°C, continued to react for 1 h, cooled to room temperature, and 1.1 times the mass of propyltrimethoxysilane was added to dissolve in ethanol, filtered, and the liquid was obtained to obtain a sealing agent; silica sol and asphalt foam material were mixed, the pH of the solution was adjusted to 6 with ammonia water, and dried at 75°C for 4 h to obtain a composite material, and then the sealing agent was heated to 10 mL / m 2 The mixture is coated on the surface of the composite material and cured at room temperature for 25 hours to obtain a heat-insulating and waterproof asphalt mixture; the mass ratio of the silica sol to the asphalt foam material is 5:1.
[0029] Example 2
[0030] (1) Grind the SBS modified asphalt until it passes through an 80-mesh sieve, heat it to 200°C in a nitrogen atmosphere, stir it at 200 rpm for 50 min, heat it to 340°C, continue stirring for 30 min, heat it to 425°C, and keep it warm for 4 h to obtain intermediate A;
[0031] (2) Grind the intermediate A until it passes through a 120-mesh sieve, add basalt fiber with a length of 6 mm, titanium boride particles with a particle size of 1.5 μm, and magnesium acetate, heat to 290° C., stir at 200 rpm for 4.5 h, and then add toluene to perform supercritical foaming treatment. The process parameters are: nitrogen gas, temperature of 300° C., and air pressure of 3 MPa to obtain an asphalt foam material; the mass ratio of the intermediate A, basalt fiber with a length of 6 mm, titanium boride particles with a particle size of 1.5 μm, magnesium acetate, and toluene is 100:7.5:7.5:0.2:0.3;
[0032] (3) TEOS, deionized water, and ethanol were mixed in a molar ratio of 1:4.5:10, heated to 60°C, stirred at 100 rpm for 55 min, and the pH of the solution was adjusted to 3.5 with hydrochloric acid to obtain silica sol; propyltrimethoxysilane, ethanol, dibutyltin dilaurate, and deionized water were mixed in a mass ratio of 20:20:0.3:4, heated to 80°C, reacted for 4 h, and the pH of the solution was adjusted to 7 with ammonia water, and then the ethanol and unreacted water were distilled off at 90°C, then heated to 110°C, continued to react for 1.5 h, cooled to room temperature, and 1.3 times the mass of propyltrimethoxysilane was added to dissolve in ethanol, filtered, and the liquid was obtained to obtain a sealing agent; silica sol and asphalt foam material were mixed, the pH of the solution was adjusted to 6.5 with ammonia water, and dried at 80°C for 6 h to obtain a composite material, and then the sealing agent was heated to 15 mL / m 2 The mixture is coated on the surface of the composite material and cured at room temperature for 40 hours to obtain a heat-insulating and waterproof asphalt mixture; the mass ratio of the silica sol to the asphalt foam material is 8:1.
[0033] Example 3
[0034] (1) Grind the SBS modified asphalt until it passes through a 80-mesh sieve, heat it to 220°C in a nitrogen atmosphere, stir it at 240 rpm for 80 min, heat it to 380°C, continue stirring for 30 min, heat it to 450°C, and keep it warm for 6 h to obtain intermediate A;
[0035] (2) Grind the intermediate A until it passes through a 150-mesh sieve, add basalt fibers with a length of 6 mm, titanium boride particles with a particle size of 3 μm, and magnesium acetate, heat to 300° C., stir at 200 rpm for 6 h, and then add toluene to perform supercritical foaming treatment. The process parameters are: nitrogen gas, temperature of 300° C., and air pressure of 3 MPa to obtain an asphalt foam material; the mass ratio of the intermediate A, basalt fibers with a length of 6 mm, titanium boride particles with a particle size of 3 μm, magnesium acetate, and toluene is 100:10:10:0.5:0.4
[0036] (3) TEOS, deionized water, and ethanol were mixed in a molar ratio of 1:4.5:10, heated to 60°C, stirred at 100 rpm for 70 min, and the pH of the solution was adjusted to 4 with hydrochloric acid to obtain silica sol; propyltrimethoxysilane, ethanol, dibutyltin dilaurate, and deionized water were mixed in a mass ratio of 20:20:0.3:4, heated to 90°C, reacted for 5 h, and the pH of the solution was adjusted to 7 with ammonia water, and then the ethanol and unreacted water were distilled off at 90°C, then heated to 110°C, continued to react for 2 h, cooled to room temperature, and 1.5 times the mass of propyltrimethoxysilane was added to dissolve in ethanol, filtered, and the liquid was obtained to obtain a sealing agent; silica sol and asphalt foam material were mixed, the pH of the solution was adjusted to 7 with ammonia water, and dried at 85°C for 8 h to obtain a composite material, and then the sealing agent was heated to 20 mL / m2 The mixture is coated on the surface of the composite material and cured at room temperature for 50 hours to obtain a heat-insulating and waterproof asphalt mixture; the mass ratio of the silica sol to the asphalt foam material is 10:1.
[0037] Comparative Example 1
[0038] The difference between Comparative Example 1 and Example 2 is that step (1) is omitted; the remaining steps are the same as those of Example 2.
[0039] Comparative Example 2
[0040] The difference between Comparative Example 2 and Example 2 is that step (2) is different. Step (2) is changed to: grind the intermediate A until it passes through a 120-mesh sieve, add basalt fiber with a length of 6 mm, titanium boride particles with a particle size of 1.5 μm, and magnesium acetate, heat to 290°C, and stir at 200 rpm for 4.5 hours to obtain an asphalt material; the mass ratio of the intermediate A, basalt fiber with a length of 6 mm, titanium boride particles with a particle size of 1.5 μm, and magnesium acetate is 100:7.5:7.5:0.2; the remaining steps are the same as Example 2.
[0041] Comparative Example 3
[0042] The difference between Comparative Example 3 and Example 2 is that step (2) is different. Step (2) is changed to: grind the intermediate A until it passes through a 120-mesh sieve, add basalt fiber with a length of 6 mm and titanium boride particles with a particle size of 1.5 μm, heat to 290°C, stir at 200 rpm for 4.5 hours, and then add toluene to perform supercritical foaming treatment. The process parameters are as follows: gas is nitrogen, temperature is 300°C, and air pressure is 3 MPa to obtain an asphalt foam material; the mass ratio of the intermediate A, basalt fiber with a length of 6 mm, titanium boride particles with a particle size of 1.5 μm, and toluene is 100:7.5:7.5:0.3; the remaining steps are the same as Example 2.
[0043] Comparative Example 4
[0044] The difference between Comparative Example 4 and Example 2 is that step (2) is different. Step (2) is changed to: grind the intermediate A until it passes through a 120-mesh sieve, add titanium boride particles with a particle size of 1.5 μm and magnesium acetate, heat to 290°C, stir at 200 rpm for 4.5 hours, and then add toluene to perform supercritical foaming treatment. The process parameters are as follows: gas is nitrogen, temperature is 300°C, and air pressure is 3 MPa to obtain an asphalt foam material; the mass ratio of the intermediate A, titanium boride particles with a particle size of 1.5 μm, magnesium acetate, and toluene is 100:7.5:0.2:0.3; the remaining steps are the same as Example 2.
[0045] Comparative Example 5
[0046] The difference between Comparative Example 5 and Example 2 is that step (2) is different. Step (2) is changed to: grind the intermediate A until it passes through a 120-mesh sieve, add basalt fiber with a length of 6 mm and magnesium acetate, heat to 290°C, stir at 200rpm for 4.5h, and then add toluene to perform supercritical foaming treatment. The process parameters are as follows: gas is nitrogen, temperature is 300°C, and air pressure is 3MPa to obtain an asphalt foam material; the mass ratio of the intermediate A, basalt fiber with a length of 6 mm, magnesium acetate, and toluene is 100:7.5:0.2:0.3; the remaining steps are the same as Example 2.
[0047] Comparative Example 6
[0048] The difference between Comparative Example 6 and Example 2 is that step (3) is different. Step (3) is changed to: propyltrimethoxysilane, ethanol, dibutyltin dilaurate, and deionized water are mixed in a mass ratio of 20:20:0.3:4, heated to 80°C, reacted for 4 hours, and the pH of the solution was adjusted to 7 with ammonia water. Then, the ethanol and unreacted water were distilled off at 90°C, and then the temperature was raised to 110°C, and the reaction was continued for 1.5 hours. After cooling to room temperature, 1.3 times the mass of propyltrimethoxysilane was added to dissolve ethanol, filtered, and the liquid was taken to obtain a sealing agent; the sealing agent was stirred at 15 mL / m 2 Apply it on the surface of the asphalt foam material and cure it at room temperature for 40 hours to obtain a heat-insulating and waterproof asphalt mixture; the remaining steps are the same as in Example 2.
[0049] Comparative Example 7
[0050] The difference between Comparative Example 7 and Example 2 is that step (3) is different. Step (3) is changed to: mix ethyl orthosilicate, deionized water and ethanol in a molar ratio of 1:4.5:10, heat to 60°C, stir at 100rpm for 55min, adjust the pH of the solution to 3.5 with hydrochloric acid to obtain silica sol; mix the silica sol and asphalt foam material, adjust the pH of the solution to 6.5 with ammonia water, and dry at 80°C for 6h to obtain an insulating and waterproof asphalt mixture; the mass ratio of the silica sol to the asphalt foam material is 8:1; the remaining steps are the same as Example 2.
[0051] Effect example
[0052] The following Table 1 shows the performance analysis results of the heat-insulating and waterproof asphalt mixtures of Examples 1 to 3 of the present invention and Comparative Examples 1 to 7.
[0053] Table 1
[0054]
[0055] From the comparison of the experimental results of the embodiment and the comparative example in Table 1, it can be found that the present invention uses SBS modified asphalt as the matrix material, and after heat treatment, the isotropic mesophase asphalt portion is increased and a relatively regular condensed aromatic hydrocarbon group structure is formed, which is beneficial for the matrix to form well-structured and evenly distributed bubbles in the supercritical foaming process, and achieve the effects of heat insulation and waterproofing. By adding magnesium elements, basalt short fibers, and titanium boride particles, mechanical support is formed at the interface, thereby preventing the bubble wall from further rupture and enhancing the stability of the structure. The basalt fibers have a large aspect ratio and the endpoints are interconnected, forming a three-dimensional network structure through mechanical contact, thereby enhancing the integrity and stability of the pore structure. Since magnesium is highly active in the melt, it can reduce the surface tension of the asphalt melt and improve the wettability of the solid components and the matrix. Magnesium has a stabilizing effect on liquid foam, which allows the bubbles to nucleate and grow rapidly, and helps the titanium boride particles to be located in the bubble wall, further enhancing the waterproofness and thermal insulation of the matrix. Then, the aerogel formed by silica sol is filled in the pore structure of the matrix, thereby reducing the porosity and enhancing the matrix's resistance to water damage. At the same time, the thermal insulation performance of the matrix is further enhanced by reducing the thermal conductivity. Next, the silicone material is used as a sealing agent, coated on the surface of the substrate, and cured into a film to form a good closed network, thereby greatly reducing the possibility of water damage to the asphalt mixture.
[0056] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and range of equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A heat-insulating and waterproof asphalt mixture, characterized in that: The heat-insulating and waterproof asphalt mixture is prepared by mixing asphalt with magnesium salt, basalt fiber and titanium boride particles, foaming the mixture, compounding the mixture with silica aerogel and finally coating the surface with a sealing agent.
2. A method for preparing a heat-insulating and waterproof asphalt mixture, characterized in that: The method comprises the following preparation steps: (1) Grind the SBS modified asphalt to pass through an 80-mesh sieve and heat to 180-220°C, 150-240 rpm stirring for 30-80 min, heating to 300-380°C, stirring for 30 min, heating to 400-450°C, keeping warm for 2-6 h to obtain intermediate A; (2) Grinding the intermediate A to pass through a 100-150 mesh sieve, adding basalt fiber, titanium boride particles, and magnesium acetate, heating to 280-300° C., stirring at 200 rpm for 3-6 hours, and then adding toluene for supercritical foaming treatment to obtain an asphalt foam material; (3) Silica sol and asphalt foam material are mixed, the pH value of the solution is adjusted to 6-7 with ammonia water, and dried at 75-85° C. for 4-8 hours to obtain a composite material. Then, a sealing agent is applied to the surface of the composite material and cured at room temperature for 25-50 hours to obtain a heat-insulating and waterproof asphalt mixture.
3. The method for preparing a heat-insulating and waterproof asphalt mixture according to claim 2, characterized in that: The length of the basalt fiber in step (2) is 6 mm.
4. The method for preparing a heat-insulating and waterproof asphalt mixture according to claim 2, characterized in that: The particle size of the titanium boride particles in step (2) is 0.5 to 3 μm.
5. The method for preparing a heat-insulating and waterproof asphalt mixture according to claim 2, characterized in that: In step (2), the mass ratio of the intermediate A, basalt fiber, titanium boride particles, magnesium acetate and toluene is 60-100:5-10:5-10:0.1-0.5:0.2-0.
4.
6. The method for preparing a heat-insulating and waterproof asphalt mixture according to claim 2, characterized in that: The process parameters of the supercritical foaming treatment in step (2) are: nitrogen gas, 300° C., and 3 MPa.
7. The method for preparing a heat-insulating and waterproof asphalt mixture according to claim 2, characterized in that: The preparation method of the silica sol in step (3) is as follows: ethyl orthosilicate, deionized water and ethanol are mixed in a molar ratio of 1:4.5:10, heated to 60° C., stirred at 100 rpm for 40 to 70 min, and the pH value of the solution is adjusted to 3 to 4 with hydrochloric acid to obtain the silica sol.
8. The method for preparing a heat-insulating and waterproof asphalt mixture according to claim 2, characterized in that: The mass ratio of the silica sol to the asphalt foam material in step (3) is 5 to 10:
1.
9. The method for preparing a heat-insulating and waterproof asphalt mixture according to claim 2, characterized in that: The preparation method of the sealing agent in step (3) is as follows: propyltrimethoxysilane, ethanol, dibutyltin dilaurate and deionized water are mixed in a mass ratio of 20:20:0.3:4, heated to 70-90°C, reacted for 3-5 hours, the pH value of the solution is adjusted to 7 with aqueous ammonia, and then the ethanol and unreacted water are distilled off at 90°C, then the temperature is raised to 110°C, the reaction is continued for 1-2 hours, cooled to room temperature, ethanol with a mass of 1.1-1.5 times that of propyltrimethoxysilane is added to dissolve, filtered, and the liquid is obtained.
10. The method for preparing a heat-insulating and waterproof asphalt mixture according to claim 2, characterized in that: The amount of the sealing agent in step (3) is 10-20 mL / m 2 .